CYP1A1 gene polymorphism and risk of endometrial hyperplasia and endometrial carcinoma. Issue 3 (1st April 2006) - Esinler, I.; Aktas, D.; Alikasifoglu, M.; Tuncbilek, E.; Ayhan, A.
Abstract : The cytochrome P4501A1 (CYP1A1) is involved in the metabolism of environmental carcinogens and estrogen. We hypothesized that CYP1A1 genetic polymorphism may be a susceptibility factor for endometrial hyperplasia (EH) and endometrial carcinoma (ECa). We therefore evaluated this hypothesis in patients with EH and ECa and control subjects using allele-specific polymerase chain reaction–based method in a Turkish population. The patients with CYP1A1 Ile/Val genotype had a fivefold higher risk of having EH than those with Ile/Ile. In contrast, a higher frequency of any Val genotype (Ile/Val and Val/Val) was found in patients with EH, indicating that persons carrying any Val allele are at increased risk for developing EH. In the ECa group, patients were also more likely to have CYP1A1 Ile/Val allele, with an adjusted odds ratio of 3.0. Moreover, there was a statistically significant increase in relative risk association with any Val genotype between patients and controls, suggesting that individuals carrying any Val genotype are at increased risk for developing ECa. We concluded that variant alleles of the CYP1A1 gene might be associated with EH and ECa susceptibility. Further studies with a large sample size should be considered to address issues of interactions between CYP1A1 and other risk factors.